Optimalisasi Pemanfaatan Lahan untuk Mendapatkan Keuntungan Maksimum Studi Kasus Pada Perumahan Manunggal Karya Di Desa Sidomulyo, Kec. Anggana, Kab. Kutai Kartanegara - Viva Oktaviani (Department of Architecture, Faculty of Engineering, 2016)
East Kalimantan province's second largest after Irian Jaya, on its own growth and development of the population is also quite rapidly so that the housing needs also felt still shortcomings and do not meet existing needs, As befits District in Kutai, District Anggana a population of not less than 28 974 the soul, is also faced with the problem of housing to meet housing needs.To get the optimum benefit compared to the cost of production of investment in housing construction Manunggal Karya Sidomulyo Village - District of Anggana are feasible so that can know the number of each type-type to be built under the land and land for public facilities. The object of research in this study is a residential development in the village Karya Manunggal Sidomulyo - Subdistrict. The required data is secondary data, ie data retrieved management Manunggal Karya developer of residential development in the village Sidomulyo - Subdistrict. And the variable used is the selling price, the building area of each type of house that will be built Based on the analysis of linear methods can be concluded that development planning II by using the ratio of 6: 1: 2: 1 in accordance with the provisions of decent government dillaksanakan for the results obtained optimum gain in the amount of Rp 21,943,350,000, - the number of housing units is as follows: type 36 = 186 units, type 54 = 31 units, type 70 = 62 units and type 98 = 31 units. The total number of 310 units with a total land area of about 35 960 m2 unused. and land for public facilities 24 040 m2.